The Problem of Conscience in Euripides’ Orestes - Dikmonienė, Jovita (Literatūra, 2017)
Euripides’ tragedy Orestes is based on the well-known myth about Orestes, son of Agamemnon, who killed his mother to avenge the death of his father and has suffered from maddening remorse since the murder of Clytemnestra (his mother). During antiquity, this play was the most cited Ancient Greek tragedy and was repeatedly performed in theatres. In 2015, Audronė Kudulytė-Kairienė was the first to translate it into the Lithuanian language. As the article explores the problem of conscience (ἡ σύνεσις, 396) in Orestes, it seeks to address the following questions: What did the people of antiquity define as conscience? What did Euripides mean by naming the suffering of Orestes conscience? What feelings are caused by conscience? Why does the town assembly not interrupt the violence and allows Orestes to continue the killing? The conclusions of the article summarize that Euripides depicted conscience as Orestes’ intuitive knowing that he had committed a crime. The poet does not reveal the origin of that knowing, but it is related to the transcendental knowledge of the truth. Euripides reveals indirectly that the knowing is instilled by the deity Erinys. The protagonist’s feelings of fear, shame and guilt are caused by conscience, and when Orestes’ mind tries to ignore these feelings, his conscience drives him mad and he has visions. Euripides’ description of Orestes’ remorse and madness intensifies the conflict in the tragedy, invites the reader to feel compassion for the protagonist and accentuates the ruthlessness of Menelaus, Tyndareus and the assembly of the Argive men. The climax of the play marks a radical shift in the mood, action, tone and characters of tragedy to reveal the paradox of the situation: the court is as violent as revenge; a person without compassion becomes even more violent; a perpetrator who fails to admit their faults to themselves or to others becomes more violent and stops hearing their “voice of conscience”. In Orestes, Euripides mocks the ruthless and revenge-like decisions of the court. At the end of the tragedy, he creates a tragicomic situation which is critiqued by researchers. Yet this specific ending reveals that a person cannot change if they are alienated and abused in their environment. Compassion and a proper relation with one’s conscience is the key to solving one’s issues. Euripides ends the tragedy with an ironic thought – if the main character’s inner voice – conscience – is silent, the tragic situation can be changed only by an “external voice” – deus ex machina.